Análise de parentesco entre filhotes da tartaruga-da-Amazônia (podocnemis expansa) provenientes de cativeiro e natureza utilizando marcadores microssatélites - Dorothy Ivila de Melo, Pereira (2013)
Popurlamente known as Turtle-the-amazon, the Giant River turtle, Podocnemis expansa is an important representative of the turtle fauna of the Amazon, her large size makes it one of the most consumed turtles by the local human population, furthermore, is an altogether marketed illegally. For these reasons, your population was reduced and currently this species is classified as low risk/conservation dependent, according to the IUCN (International Union for Conservation of Nature). As a conservation measure, to ease the pressure of capture in nature, this species can be commercially maid in captivity. However, the lack of technical support regarding captivity important ecological information about the biology of the species hinders their proper management. In this context, the aim of this study was to determine, based on the analysis of relationship of clutch, the type of reproductive behavior in this species about samples of captivity and nature. Blood samples were collected by puncture of the femoral vein, of 191 offspring in captivity, from Fazenda São Francisco, Manacapuru-AM and 165 hatchlings from the Juruá, Carauari-AM. We genotyped a total of 356 offspring added two locations using 5 microsatellite loci. The analysis of the loci revealed 100% occurrence of multiple paternity both in captivity and in nature. The markers used in this study were quite polymorphic and highly discriminatory power for the analysis of kinship with identity values (I) IC=1,08 x 10-6 for samples of captivity and IC= 2,85x10-6 for samples of nature, and the probability of paternity exclusion (Q) QC = 99.9% in both cases, indicating the detection power paternity multiple of these loci used. The allele counting method, it is possible to estimate the number of males that were contributing each offspring, was observed contribution of at least 10 males from nests two in captive and nine males in one of the nests of nature. These results also reveal the ability of females of this species have in store sperm from multiple matings. Knowledge about the type of behavior that this species has is fundamental and has great implications when considering the conservation of P. expansa, the data obtained in this study will contribute to support the management and conservation programs suitable for this species, both natural populations and for the captivity